BLOCKING OF CUSTOMER ACCOUNTS WITH SUSPECT STATUS IN MONEY LAUNDERING CRIME CASES (TPPU) - Delfy Dyan Yessy Simanjuntak (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
Â The purpose of this study is to analyze the arrangements regarding the deadline for blocking the accounts of customers suspected of money laundering offenses that have accommodated the value of justice. The method used is the Normative Legal Research Method with the Type of Research Obscurity of Norms in Article 12 Paragraph (Bank Indonesia Regulation Number 2/19/PBI/2000) concerning Requirements and Procedures for Giving Written Orders or Permits to Open Bank Secrets (PBI 2/19/2000) 2000). The results of this study are related to the blocking time limit for a period of 30 days. The basis for blocking ML accounts is to facilitate investigations in checking the flow of funds in order to reveal the truth about a fund owned by a customer.